Eksplorasi cendawan endofit pada akar tanaman karet (Hevea brasiliensis Muell. Arg.) sebagai agens hayati jamur akar putih (Rigidoporus microporus (Swartz; Fr)) di kabupaten Asahan - Inni Izzati; Lahmuddin Lubis; Hasanuddin Hasanuddin (Jurnal Agroekoteknologi, 2019)
ABSTRACT Endophytic fungi are known be able to produce secondary metabolites that often impact on the growth of its host, such as enhance its growth and increasing the resistance of plant to biotic and abiotic stress condition. This research was aimed to isolate and test endophytic fungi which have potency as biocontrol agents against Rigidoporus microporus on rubber tree. The research was conducted at Plant Disease Laboratory, Program Study of Agrotechnology, Faculty of Agriculture, Universitas of Sumatera Utara, Medan from September 2017 to February 2018. It was done by using Completely Randomized Design (CRD) Non Factorial.  The results indicated there were 8 genus of fungi  (Rhizoctonia sp., Penicillium sp., Gliocladium sp., Trichoderma sp., Aspergillus sp., Rhizopus sp., Mucor sp. dan Fusarium sp.) from roots of rubber tree in Asahan that have potency as biological agent to control R. microporus in rubber tree. The best results were obtained on genus Aspergillus sp. with inhibition zone was 81,11%.